KEDUDUKAN BPKP DALAM MENGAUDIT KERUGIAN KEUANGAN NEGARA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR: 31/PUU-X/2012 - Gusman, Erry (Ensiklopedia Sosial Review, 2019)
State financial losses are those caused by unlawful acts or acts that abuse the authority, opportunity or means available to someone due to their position or position and this is done in conjunction with acts of enriching oneself or another person or a corporation. Conflict of authority related to the assessment of state financial losses in handling corruption cases, answered by the issuance of the Constitutional Court Decision Number 31 / PUU-X / 2012 dated October 23, 2012. Polemics related to the authority to calculate state losses in handling corruption cases are answered with the issuance of Decision of the Constitutional Court (MK) Number 31 / PUU-X / 2012 dated October 23, 2012. For this reason the authors are interested in examining how the role of BPKP in auditing state finances after the MK decision. This study uses normative juridical writing methods. After the writer conducted the research, the writer concluded that: 1) BPKP's position after the Constitutional Court's decision, acknowledged the authority of BPKP in conducting an investigative audit; 2) The impact of BPKP's audit results as a basis for calculating the losses of state finances can be seen from the BPKP's repressive strategy. The repressive strategy carried out by BPKP had an impact in terms of conducting investigative audits carried out on the handling of cases that were strategic, significant, material and received public scrutiny. In repressive efforts, the role of BPKP is not limited to conducting audits; 3) To optimize BPKP audit results as a basis for calculating state financial losses in preventing money laundering, BPKP in accordance with Government Regulation No. 60/2008 concerning Government Internal Control Systems and Presidential Regulation No. 192/2014 can conduct internal supervision through audits including audits investigative.